Assessment of Physician's Knowledge of Potential Drug-Drug Interactions: An Online Survey in China - Yuan, Jing; Shen, Chunying; Wang, Chengnan; Shen, Gang; Han, Bing (Frontiers in Medicine, 2021)
Background: Drug interactions are the most common preventable cause of adverse drug reaction, which may result in drug toxicity or undesired therapeutic effect with harmful outcomes to patients. Given the rising use of combination therapies, the main objectives of this study were to estimate the degree to which physicians can identify potential drug-drug interactions (PDDIs) correctly and to describe the common source of information used by physicians when they need to check PDDIs. Methods: A cross-sectional survey utilizing a self-administered online questionnaire was conducted among physicians in China. Participants were asked to classify 20 drug pairs as “no interaction”, ‘may be used together with monitoring”, “contraindication”, and “not sure”. We also collected data on the physician’s source of information and altitude toward the PDDIs. An ordinary least square regression model was performed to investigate the potential predictors of PDDI knowledge. Results: Eligible questionnaires were obtained from 618 physicians. The respondents classified correctly 6.7 out of 20 drug pairs, or 33.4% of the drug interactions investigated. The number of drug pairs recognized by respondents was ranged from 0 to 16. The percentage of physicians who recognized specific drug pairs ranged from 8.3% for no interactions between conjugated estrogens and raloxifene, to 64.0% for the interaction between dopamine and phenytoin. When the respondents want to check PDDI information, the most commonly used source of information was package inserts (n=572, 92.6%), followed by the Internet or mobile Apps (n=424, 68.6%), consultation with clinical pharmacists (n=384, 62.1%), medical textbooks (n=374, 60.5%), knowledge base in Chinese (n=283, 45.8%), and other physicians (n=366, 59.2%). In the multiple regression analysis, the significant predictors of a higher number of recognized drug pairs were years of practice and altitudes towards PDDIs. Conclusion: In this online survey accessing physician’s ability to detect PDDIs, less than half of the drug pairs were recognized, indicating unsatisfactory level of knowledge about the clinically significant drug interactions. Continuing education and accessible electronic database can help physicians detecting PDDIs and improve drug safety.